2022
DOI: 10.1101/2022.11.14.22282145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of regulatory compliance in health and social care services: a systematic review using the Consolidated Framework for Implementation Research

Abstract: Background The delivery of high quality care is a fundamental goal for health systems worldwide. One policy tool to ensure quality is the regulation of minimum standards by an independent public authority. This systematic review seeks to identify determinants of compliance with such regulation in health and social care services.  Methods Systematic searches were carried out on five electronic databases and grey literature sources. Quantitative, qualitative and mixed methods studies were eligible for inclusion.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 241 publications
(822 reference statements)
0
1
0
Order By: Relevance
“…More research is also needed on the variance in performance in successful implementation, to understand who is more or less likely to be successful in making and sustaining change. A recent study examining the determinants of regulatory compliance in health and social care services, largely drawing on studies of nursing homes, found higher compliance in smaller facilities and those with higher nurse staffing levels and lower turnover 7. More studies examining variation in performance, the factors associated with variance and examination of the characteristics of positive deviants will strengthen our understanding of implementation and improve the likelihood that organisations can succeed in meeting both external demands and internal drivers to increase safety and quality.…”
Section: Moving Forwardmentioning
confidence: 99%
“…More research is also needed on the variance in performance in successful implementation, to understand who is more or less likely to be successful in making and sustaining change. A recent study examining the determinants of regulatory compliance in health and social care services, largely drawing on studies of nursing homes, found higher compliance in smaller facilities and those with higher nurse staffing levels and lower turnover 7. More studies examining variation in performance, the factors associated with variance and examination of the characteristics of positive deviants will strengthen our understanding of implementation and improve the likelihood that organisations can succeed in meeting both external demands and internal drivers to increase safety and quality.…”
Section: Moving Forwardmentioning
confidence: 99%